Examination of the relationship between business model components and business performance: A comparative study on selected foodpreneurs - Cheng, Jason Marvin N. (Animo Repository, 2022)
The COVID-19 pandemic has affected several businesses across various industries here in the Philippines and around the world. The food service business was not spared from this tragedy as many were forced to close down. However, there were a few foodpreneurs who rose to the occasion to take drastic action to ensure the survival and continuity of their business operations. This study hopes to understand better the business model put in place by these foodpreneurs to influence a favorable business performance on their end. To execute this study, the research made use of a multiple embedded case study research design. This entailed collecting data from various personalities within the business to make sense of the various components of their business model and business performance. Based on the findings, the study has shown that the various business model components have in some way influenced the business performance of each foodpreneur’s businesses. Most of the business model components across businesses have some glaring similarities and differences across the foodpreneurs’ businesses. The most prominent ones involve the key partners, key activities, and key resources used by each of them. The study also found that there was a significant embrace to new digital technologies such as social media, food delivery applications, and digital marketing at large. While it was expected that the financial performance of some of the foodpreneur’s businesses, the other dimensions of business performance performed well across all four cases. Suggestions for each of the four companies and for future research are provided.